Simulation-Based Training in High-Quality Cardiopulmonary Resuscitation Among Neonatal Intensive Care Unit Providers - Parikh, Pratik; Samraj, Ravi; Ogbeifun, Henry; Sumbel, Lydia; Brimager, Kelli; Alhendy, Mohammed; McElroy, James; Whitt, Dottie; Henderson, Cody; Bhalala, Utpal (Frontiers in Pediatrics, 2022)
Introduction: American Heart Association guidelines recommend the use of feedback devices for CPR provider resuscitation training. There is paucity of published literature regarding the utility of these devices especially in neonates and infants. We sought to evaluate if simulation-based education and debriefing using a CPR feedback device would improve CPR performance on an infant manikin in a cohort of NICU nurses as evaluated by CPR feedback device. Methods: We conducted a prospective, observational simulation study to assess the quality of chest compressions by NICU nurses before and after debriefing using CPR quality data captured by an accelerometer-based device. Chest compression (CC) depth, rate, recoil, CC fraction and nursing confidence level related to performing a high-quality CPR were compared before and after debriefing using paired t-test and Wilcoxon rank sum test. Results: A total of 62 NICU nurses participated in the study and all of them were Neonatal Resuscitation Program (NRP) certified. There was a significant improvement in CC depth and CC fraction [mean + SD values = 0.79 in + 0.17 (pre-debrief), 0.86 in + 0.21 (post-debrief) (p = 0.034) and 56.8% + 17.7 (pre-debrief), 70.8% + 18.4 (post-debrief) (0.0014), respectively]. There was no difference in CC rate (p= 0.36) and recoil (p= 0.25) between pre and post structured debriefing. The confidence level of nurses in all CPR dynamics (appropriate CC rate, CC depth, team communication, minimizing interruption in CC and coordinating CC with ventilation) was significantly higher after simulation and structured debriefing. All the nurses used 3:1 compression: ventilation ratio of NRP despite the patient being a 4 month old premature baby in the NICU. Conclusions: Simulation training and debriefing of NICU nurses using CPR feedback device improved their chest compression quality on an infant mannequin and their confidence level for performing high-quality CPR. NICU providers tend to use NRP protocol of 3:1 compression: ventilation ratio during CPR in the NICU irrespective of age of the infant.